Impact of Herding Behavior on Investment Decisions in the Nepalese Stock Market with Mediation and Moderation Effects - Rana, Bikash (International Research Journal of MMC, 2024)
This research examines the influence of herding behavior on investment decisions made in Nepal, with the moderating role of financial literacy and overconfidence as a mediating factor. Traditional financial theories suggest that rational investors make decisions based on available information to maximize their capital. In contrast, behavioral finance argues that psychological factors significantly impact financial decisions. Data were collected from 384 investors trading on the Nepal Stock Exchange using a structured survey. The findings indicate that herding behavior significantly enhances both overconfidence and investment decisions. Overconfidence has a positive impact on investment decisions. Financial literacy acts as a positive moderator, while overconfidence serves as a positive mediator between herding behavior and investment decisions. SMART-PLS was employed for data analysis.